2013
DOI: 10.1117/12.2024018
|View full text |Cite
|
Sign up to set email alerts
|

SiC multi-layer protective coating on carbon obtained by thermionic vacuum arc method

Abstract: SiC single-layer or multi-layer on C used to improve the oxidation resistance and tribological properties of C have been obtained by Thermionic Vacuum Arc (TVA) method. The 200nm thickness carbon thin films was deposed on glass or Si substrate and then 100÷500 nm thickness SiC successively layers on carbon thin film was deposed. The microstructure and mechanical characteristics of as-prepared SiC coating were investigated by Transmission Electron Microscopy (TEM, STEM), Energy Dispersive X-Ray Spectroscopy (ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…1-cathode, 2crucible 3-material to be deposited 4-holder with substrates 5-thickness monitor This simplest arrangement, one electron gun and one crucible, is applicable also in cases when the intention is to deposit a film from several materials, which can be put together into one crucible; see e.g., ref. [36][37][38][39][40].…”
Section: One Electron Gun and One Cruciblementioning
confidence: 99%
See 1 more Smart Citation
“…1-cathode, 2crucible 3-material to be deposited 4-holder with substrates 5-thickness monitor This simplest arrangement, one electron gun and one crucible, is applicable also in cases when the intention is to deposit a film from several materials, which can be put together into one crucible; see e.g., ref. [36][37][38][39][40].…”
Section: One Electron Gun and One Cruciblementioning
confidence: 99%
“…In ref. [37][38][39][40] were studied silicon-carbide multilayer protective coatings at temperatures up to 1000 • C. Measurements showed that the third layer acts as a stopping layer for oxygen. Characterization of ternary C-Si-Al nanocomposite thin films obtained by TVA presented in [122].…”
Section: Binary and Ternary Combinationmentioning
confidence: 99%